DFT analysis of intermolecular and intramolecular double proton transfer during the condensation process of 4-pyridinecarboxaldehyde with isomers of aminobenzoic acid - Ion Arsene; Viorica Purcel (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
To understand in detail the double proton transfer in the condensation reaction of 4-pyridinecarboxaldehyde with isomers of aminobenzoic acid (in the gas phase and in solvent), the dynamic mechanism was studied using the DFT method implemented in the GAUSSIAN 09 program and the 6-31G basis set. All condensation processes described in this study proceed in two stages: the first stage involves the interaction of the reactants and the methanol-mediated proton transfer from the amine group to the aldehyde group, forming an intermediate compound; the second stage is identified by the intramolecular donation of the second proton from the (-NH) group to the hydroxyl oxygen, forming highly stable Schiff base products with the elimination of water and methanol molecules. From the perspective of activation energy, it is observed that the solvent has a positive influence on intermolecular transfer, which is not the case for intramolecular transfer. Additionally, the solvent positively contributes to the energetic stability of the final reaction products.